Health‐related quality of life and depression in a sample of Latin American adults with rheumatoid arthritis. (7th October 2014) - Senra, Hugo; Rogers, Heather; Leibach, Gillian; Altamar, Marvín L. P.; Plaza, Silvia L. O.; Perrin, Paul; Durán, Maria A. S.
Abstract: Objective: To compare the health related quality of life (HRQoL) and depression of individuals with rheumatoid arthritis (RA) to healthy controls in Colombia, as well as to examine the connections between these two variables in individuals with RA. Method: One hundred and three individuals with RA were recruited from ambulatory centers in Colombia. Seventy‐three control participants were recruited from the local community. Both groups differed with respect to age, gender and marital status ( P < 0.001), while education and socio‐economic levels were similar. HRQoL was assessed using the Short Form‐36 (SF‐36) and depressive symptoms were assessed using the Patient Health Questionnaire‐9 (PHQ‐9). Results: A multivariate analysis of covariance found that RA patients reported substantially higher depressive symptoms and lower HRQoL than healthy controls ( P < 0.01 and P < 0.05, respectively). The effect sizes of the differences between patients and controls in HRQoL and depressive symptoms were all large. All SF‐36 HRQoL variables were significantly correlated with depressive symptoms in patients and controls ( P < 0.05). Social functioning and vitality were uniquely associated with depressive symptoms in the RA group ( P < 0.01 and P < 0.05, respectively), whereas education and social functioning were uniquely associated with depressive symptoms in controls ( P < 0.05 and P < 0.005, respectively). Conclusions: Research indicates that individuals with RA have deteriorated HRQoL, and this study extends these findings to a Colombian sample and highlights the importance of the independent relationship between depressive symptoms and vitality in this group of Colombians with RA.